Single photon counting in brillouin laser light scattering experiments - BŁACHOWICZ, T. (Archives of Acoustics, 1999)
What follows is a description of the electronics and simple mechanical equipment needed for single photon counting. It is intended as an introduction and guide to assist users in the measurement of Brillouin laser light scattering on acoustic hypersonic waves. Simple method of a numerical filtration of the low-intensity-level optical signal is described in detail.